Using the Theory of Practice Architectures to establish what it means to “do” learning design, and the arrangements that enable and constrain practice - Olney, Tom; Wood, Carlton (Frontiers in Education, 2023)
In the past decade learning design has become a widely adopted field of practice for higher education institutions (HEI) engaged with producing online and distance learning materials. To date, much has been written about the conceptual principles of guidance, representation and sharing that underpin learning design, and the theoretical frameworks, models, tools, and instruments that have also been developed to support it. However, little analysis has been done to describe learning design in the specific sites of practice into which it has been introduced, or to describe the arrangements that might enable or constrain the embedding of this digital learning innovation by the people tasked with doing so. This original research article utilizes the Theory of Practice Architectures (TPA) as a theoretical approach to establish what learning design practice is composed of, and how that practice is shaped by its multiple sites of practice in the STEM faculty of a large open and distance learning HEI. The analysis draws on evidence -captured longitudinally over four years -from surveys (n=43), learning design analytics (n=20), in-depth interviews with key stakeholders (n=14), document analysis and learning design workshop data (n=28) about the journey of 28 modules from conceptualization to faculty approval for full module production. The application of TPA to this extensive data set offers new and under discussed identification of key challenges experienced in the adoption of learning design approaches. In the sites of practice explored here, two specific arrangements are discussed: time, and the legacy of the Open University Learning Design Initiative (OULDI). Both can be seen to constrain and enable practice in different ways. This study will be relevant for scholars and researchers attempting to evaluate current learning design approaches or looking to explore more accurate ways of describing what it means to 'do' learning design, both now and in the future.